Advances in genome sequencing reveal changes in gene content that contribute to arthropod macroevolution - Cheatle Jarvela, Alys M.; Wexler, Judith R. (Development Genes and Evolution, 2023)
Current sequencing technology allows for the relatively affordable generation of highly contiguous genomes. Technological advances have made it possible for researchers to investigate the consequences of diverse sorts of genomic variants, such as gene gain and loss. With the extraordinary number of high-quality genomes now available, we take stock of how these genomic variants impact phenotypic evolution. We take care to point out that the identification of genomic variants of interest is only the first step in understanding their impact. Painstaking lab or fieldwork is still required to establish causal relationships between genomic variants and phenotypic evolution. We focus mostly on arthropod research, as this phylum has an impressive degree of phenotypic diversity and is also the subject of much evolutionary genetics research. This article is intended to both highlight recent advances in the field and also to be a primer for learning about evolutionary genetics and genomics.